Decentralized public-funded oral rehabilitation programs and oral health-related quality of life of the elderly in Rural Kerala - Vivek Narayan; Mary Shimi S. Gomez; Susan Thomas; Arun Rao; S Anilkumar; Indu Raj; Vidhya Parameswaran (Wolters Kluwer Medknow Publications, 2021)
Background: Edentulism among the elderly deteriorates the physical, social, and mental dimensions of oral and general health. Objectives: This study compared the changes in oral health-related quality of life (OHRQoL) of the edentulous elderly following prosthetic rehabilitation with complete dentures among beneficiaries of public denture programs. The study also compared the responsiveness of Oral Health Impact Profile-14 (OHIP-14) and Geriatric Oral Health Assessment Index (GOHAI). Methodology: This prospective pre-post comparison study was conducted among beneficiaries of two public-funded oral rehabilitation programs (P1 and P2) organized by local self-government institutions. OHRQoL was recorded using OHIP-14 and GOHAI in P1 and P2, respectively. Data collection was done at baseline using direct interview and 4 weeks after denture insertion using telephonic interview. Wilcoxon signed-rank tests were used to compare differences in responses between baseline and posttreatment. Statistical significance was considered at P < 0.05. Psychometric properties of tools were determined using Cronbach's alpha and exploratory factor analysis. Results: The mean change in OHIP-14 and GOHAI at 4 weeks after denture insertion was 15.39 ± 12.61 and 10.73 ± 8.71, respectively (P < 0.05). Cronbach's alpha for the modified OHIP-14 and GOHAI scales was 0.73 and 0.65, respectively. Conclusions: Prosthetic dental rehabilitation provides psychological, social, and functional benefits to the edentulous elderly. Public-funded denture programs are effective to improve OHRQoL among the edentulous elderly from a poor socioeconomic background.